1998
DOI: 10.1172/jci2687
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated clearance of periciliary liquid and mucus from airway surfaces.

Abstract: Airway surface liquid is comprised of mucus and an underlying, watery periciliary liquid (PCL). In contrast to the well-described axial transport of mucus along airway surfaces via ciliary action, theoretical analyses predict that the PCL is nearly stationary. Conventional and confocal microscopy of fluorescent microspheres and photoactivated fluorescent dyes were used with well-differentiated human tracheobronchial epithelial cell cultures exhibiting spontaneous, radial mucociliary transport to study the move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
326
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(352 citation statements)
references
References 31 publications
23
326
2
1
Order By: Relevance
“…Human tracheo-bronchial epithelial cells (CF and normal) were isolated and cultured under air-liquid conditions as previously described (38). Mucus harvested from Ϸ200 concurrent cultures was pooled and stored at 4°C.…”
Section: Methods Preparation Of Concentrated Mucusmentioning
confidence: 99%
“…Human tracheo-bronchial epithelial cells (CF and normal) were isolated and cultured under air-liquid conditions as previously described (38). Mucus harvested from Ϸ200 concurrent cultures was pooled and stored at 4°C.…”
Section: Methods Preparation Of Concentrated Mucusmentioning
confidence: 99%
“…Further studies in human tracheobronchial epithelial cultures (Matsui et al, 1998) recently demonstrated that the entire periciliary fluid is transported at approximately the same rate as mucus (about 40 mm/s), and that the removal of the mucous layer reduced periciliary fluid transport by more than 80%. The cephalad movement of periciliary liquid along airway epithelial surfaces makes this mucus-driven transport an important component of salt and water physiology in the lungs.…”
Section: Mucociliary Clearancementioning
confidence: 99%
“…Thickened secretions caused by improper regulation of airway surface liquid contribute to the accumulation of mucus in the airway and defective mucociliary clearance (2). Retained mucus plugs provide a niche for bacterial colonization and persistence.…”
mentioning
confidence: 99%